Ozone in Dental Therapy - Chickanna, Rudrakshi (The Journal of Dentists, 2016)
A literature search was performed using MEDLINE (PubMed) and other electronic basis from 1991 to 2014. Search included books and journals based on the systematic and critical reviews, in vitro and in vivo clinical studies on Ozone therapy in dentistry. Ozone has been shown as powerful oxidizing agent capable of interacting as metabolic, immune modulator as well as an antimicrobial agent. It has been used to stimulate remineralisation of recent caries-affected teeth, as a preventive therapy in caries, root caries, intra-canal irrigants in endodontic treatment, treatment of alveolitis, avascular osteonecrosis of the jaw, herpes virus infection, to inhibits plaque formation, an adjuvant in periodontal surgical and maintenance phase and to disinfect implant surface and treat peri-implantitis and in water line to disinfect water.